Pengelompokan Tanaman Perkebunan Berdasarkan Produktivitas dan Luas Lahan dengan K- Means Clustering - Ethaniel Williano Adhi Putra; Yunus Widjaja (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Plantation data in West Java was grouped based on land area and crop productivity using the K-Means method. This data was obtained from Open Data Jabar from 2022 to 2024 and analyzed using a quantitative approach. Three groups can be identified based on the clustering results: one group has high productivity but relatively limited land area, another has large land area but suboptimal productivity, and the last group has equally low productivity and land area. The results indicate that land area does not always correlate with productivity. This study emphasizes the importance of selecting relevant variables and using methods consistently to produce more accurate and understandable analyses.